Nitrogen diffusion and interaction with dislocations in single-crystal silicon - Alpass, C; Murphy, J; Falster, R; Wilshaw, P (2009)
The results of dislocation unlocking experiments are reported. The stress required to unpin a dislocation from nitrogen impurities in nitrogen-doped float-zone silicon (NFZ-Si) and from oxygen impurities in Czochralski silicon (Cz-Si) is measured, as a function of the unlocking duration. It is found that unlocking stress drops with increasing unlocking time in all materials tested. Analysis of these results indicates that dislocation locking by nitrogen in NFZ-Si is by an atomic species, with a similar locking strength per atom to that previously deduced for oxygen atoms in Cz-Si. Other experiments measure dislocation unlocking stress at 550 °C in NFZ-Si annealed at 500-1050 °C. The results allow an effective diffusivity of nitrogen in silicon at 500-750 °C to be inferred, with an activation energy of 3.24 eV and a diffusivity prefactor of approximately 200 000 cm2 s-1. This effective diffusivity is consistent with previous measurements made at higher temperatures using secondary ion mass spectrometry. When the results are analyzed in terms of a monomer-dimer dissociative mechanism, a nitrogen monomer diffusivity with an activation energy in the range of 1.1-1.4 eV is inferred. The data also show that the saturation dislocation unlocking stress measured at 550 °C in NFZ-Si is dependent on the anneal temperature, peaking at 600-700 °C and falling toward zero at 1000 °C. © 2009 American Institute of Physics.